Difficult airway management in a patient with mucopolysaccharidosis type IVA (Morquio A syndrome): a case report - Aleyna Calap Ocak; Şemsi Mustafa Aksoy; Burak Nalbant (Journal of Comprehensive Surgery, 2026)
Mucopolysaccharidosis type IVA (Morquio A syndrome) is a rare lysosomal storage disorder characterized by glycosaminoglycan accumulation, resulting in progressive skeletal deformities and significant airway abnormalities that pose major challenges during anesthetic management. Airway-related complications remain a leading cause of perioperative morbidity and mortality in these patients. We report the perioperative airway management of a 27-year-old woman with mucopolysaccharidosis type IVA who underwent elective posterior cervical laminectomy for cervical myelopathy secondary to odontoid hypoplasia. Despite a preoperative Mallampati score of II, tracheal intubation proved to be unexpectedly difficult. Initial attempts using a videolaryngoscope and a Macintosh laryngoscope failed because of a markedly enlarged and thickened epiglottis, which prevented adequate visualization of the glottic opening. Successful tracheal intubation was ultimately achieved using a Miller laryngoscope, which allowed direct elevation of the epiglottis and clear visualization of the vocal cords. Anesthesia was maintained with total intravenous anesthesia, and the patient was extubated after complete recovery of consciousness and a successful cuff leak test. In the early postoperative period, upper airway edema developed but resolved promptly with medical treatment without requiring reintubation. This case highlights that conventional preoperative airway assessment may underestimate the difficulty of tracheal intubation in patients with MPS type IVA. Although videolaryngoscopy is generally recommended as the first-line technique for anticipated difficult airway management, it may be insufficient in patients with severe supraglottic soft tissue hypertrophy. Maintaining the availability of multiple airway devices, including a Miller laryngoscope, together with meticulous perioperative planning and close postoperative monitoring, is essential for the safe anesthetic management of these patients.